2017
DOI: 10.1093/ofid/ofx142
|View full text |Cite
|
Sign up to set email alerts
|

Feasibility of Treating Hepatitis C in a Transient Jail Population

Abstract: Jails represent a critical component of the public health response to HCV elimination. We report on outcomes of 104 patients receiving HCV treatment from January 1, 2014 to June 30, 2016 in a large urban jail setting. Our data demonstrate that treatment in jails is feasible, but many barriers remain.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
24
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 27 publications
(26 citation statements)
references
References 5 publications
(5 reference statements)
2
24
0
Order By: Relevance
“…Thus, efforts should be made to offer a broader HCV treatment access to PWID with a final aim of preventing efficiently further transmission. Jail constitutes a critical component of the public health response to HCV eradication and recent studies suggest that DAA therapy in jail is feasible and the access to DAA may preserve the efficacy of community‐initiated HCV regimens …”
Section: Discussionsupporting
confidence: 91%
“…Thus, efforts should be made to offer a broader HCV treatment access to PWID with a final aim of preventing efficiently further transmission. Jail constitutes a critical component of the public health response to HCV eradication and recent studies suggest that DAA therapy in jail is feasible and the access to DAA may preserve the efficacy of community‐initiated HCV regimens …”
Section: Discussionsupporting
confidence: 91%
“…Implementing DAA therapy for HCV has been successful with high cure rates in prison settings [ 14 ], but little has been published from jail settings. Treatment with DAA therapy in NYC jails is feasible as reported in a prior study from our system [ 15 ], but this study did not report SVR12 data and surveillance for reinfection events, due to lack of longitudinal follow-up.…”
mentioning
confidence: 99%
“…Despite the quick turnover and inability to administer and track the full course of DAAs, short-term correctional settings serve as an opportunity to continue HCV-care for those already on treatment but also have the potential to engage a large number of individuals unaware of their status into care, and provide testing and education for those at risk for HCV. A study conducted in the New York City jail system found viral load suppression for over 90% of patients including those who initiated treatment prior to incarceration and those who initiated treatment in the jails, demonstrating the feasibility of DAA access in short-term settings [ 8 ].…”
Section: The Hcv Care Cascade In Correctional Settings: Missed Opportmentioning
confidence: 99%